The relationship between leader-member exchange, organizational inflexibility, perceived organizational support, interactional justice and organizational citizenship behaviour - Asgari, Ali; Silong, Abu Daud; Ahmad, Aminah; Abu Samah, Bahaman (Academic Journals, 2008)
It has been proposed that issues of organizational behaviours should be incorporated in the study for predicting subordinate citizenship behaviour. This research had one objective: to assess the impact of four behaviours – leader-member exchange, organizational inflexibility, perceived organizational support and interactional justice – on organizational citizenship behaviour. The subjects of this study were all full-time employees with their managers who working in the educational organization in Iran. This study surveyed 220 respondents. The sampling frame of the respondents was obtained from educational organization in Shiraz city in Iran. Data were collected on a structured questionnaire containing standard scales of transformational leadership behaviours, LMX, and organizational citizenship behaviours. After establishing the psychometric properties of the scales, hypotheses were tested through statistical analysis of the data. Results indicate that four variables are more likely to predict citizenship behaviour.